El "fresno americano" presente en la Argentina es Fraxinus pennsylvanica (Oleaceae) - Achinelli, Fabio Germán (1999)
The “american ash" present in Argentina is Fraxinus pennsylvanica (Oleaceae). In Argentina the species known as “american ash’’ (Fraxinus pennsylvanica Marshall, F. americana L.) have been difficult to determine because of their morphological similarity. To establish the correct identity of the materials growing at the country, taxonomic and micromorphologic observations were carried out. All of the specimens of “american ash’’ analyzed, both naturalized and cultivated, were determined as F. pennsylvanica Marshall subesp.pennsylvanica G. N. Mill, and F. pennsylvanica Marshall subesp. velutina (Torr.) G. N. Mill. Accordingly we conclude that F. americana is not present in Argentina.